Pengaruh Kondisi Sosial, Ekonomi, dan Ketenagakerjaan terhadap Migrasi Luar Negeri di Indonesia : (Studi Kasus: 33 Provinsi di Indonesia Tahun 2013 – 2022) - Mangara, Togi Haidat; Saputri, Wadi; Putri, Rahmi Aulia (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
The large number of Indonesian workers who have been sent abroad has made Indonesia known as a source of international migrant workers and has become an interesting phenomenon in overcoming labor problems in Indonesia. The aim of this research is to examine and analyze the influence of poverty, economic growth, unemployment, education, and population growth partially and simultaneously on workers who migrate to other countries based on 33 provinces in Indonesia in 2013 - 2022. The type of data used is secondary data sourced from BP2MI and BPS. Based on the regression results using the Generalized Method of Moments (GMM) method, it is stated that there is a positive and significant relationship between international migration lag and population density on international migration. Furthermore, the variables poverty, economic growth and education have a negative and significant relationship to international migration. However, the unemployment variable does not have a significant relationship with international migration.